Elaboration of brittleness curves of walls of limited ductility of 10 cm. thick, based on experimental tests; period 2011 - 2015. - Cotrado Flores, Dina Marlene (2017)
The present research aimed to contribute to seismic vulnerability in buildings of limited ductility walls. For this, fragility curves have been developed in walls of limited ductility of 10 cm of thickness according to the PACT of the P-58 FEMIA. Data were collected from 20 experimental tests carried out in the structure laboratory of the Peruvian Center for Seismic Investigation and Disaster Mitigation of the National University of Engineering. Fragility curves express the probability that a limited ductility wall will reach or exceed a selected damage state for a given drift or displacement level. From the fragility curves it ¡is possible to observe that the probability of exceeding 50% of damaging state 2 (maximum wall strength) is: 13mm for MDL-CCA1, 16mm for MDL-CCA2, 20mm for MDL- 2mm for MDL-CCA9, 4mm for MDL-CCA5, 4mm for MDL-CCA6, 5mm for MDL-CCA7, 4mm for MDL-CCA8, and 4mm for MDL-CCAS9. It is concluded that the fragility curves developed in this project are a very useful tool for further studies of seismic vulnerability evaluation in buildings of walls of limited ductility of 10 cm thickness.